Laudian and Royalist polemic in seventeenth-century England : the career and writings of Peter Heylyn. - Milton, Anthony (Politics, Culture & Society in Early Modern Britain., 2007)
This is the first full-length study of one of the most prolific and controversial polemical authors of the seventeenth century. It provides for the first time a detailed analysis of the ways in which Laudian and royalist polemical literature was created, tracing continuities and changes in a single corpus of writings from 1621 through to 1662. In the process, the author presents important new perspectives on the origins and development of Laudianism and?Anglicanism? and on the tensions within royalist thought. Milton?s book is neither a conventional biography nor simply a study of printed work.